Self-Efficacy Mediation the Influence of the Family Environment and Metacognitives on Student Academic Performance - Hari Mulyadi; Ikaputera Waspada; Sundanis Kencana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The research is based by the low students academic performance of economics subject in Senior High School in Sumedang Regency. The purpose of this study was to study and analyze the effect of family environment on self-efficacy, the effect of metacognitive on self-efficacy, the effect of self-efficacy on students academic performance, and the effect of family environment and metacognitive on students academic performance mediated by self-efficacy. The method used in this research is explanatory survey research with data collection techniques through questionnaires and observation. The population of this research is 1.767 students senior high school in Sumedang Regency, while the sample of 231 students. The collected data is analyzed using descriptive statistical analysis and path analysis. The result shows that: (i) the students family environment is in the high category, while the level of metacognitive, self-efficacy, and academic performance of students is in the medium category. (ii) family environment affects self-efficacy. (iii) metacognitive affects self-efficacy. (iv) self-efficacy affect students academic performance. (v) family environment affects academic performance direcly and indirectly through self-efficacy. (vi) metacognitive affects academic performance direcly and indirectly through self-efficacy.